Exchange Rate, Money, and Wages : What is Driving Prices in Armenia? - Khachatryan, Armine (IMF Working Papers; Working Paper ;, 2004)
This paper is the first attempt to look at inflation dynamics and monetary transmission mechanisms in Armenia in the context of a full information model containing three interrelated markets: foreign exchange, money, and labor. Using the vector error correction model (VECM) approach, we find that the exchange rate pass-through to prices is very strong relative to credit, wage, and interest rate channels. The analysis suggests a relatively fast adjustment of prices to long-run disequilibria in the exchange rate market, albeit with initial overshooting of the price level. In addition, we find no evidence of prices responding to changes in money and wages in a statistically significant manner.